RANCANG BANGUN SISTEM INFORMASI PRODUKSI CUSTOM FURNITURE BERBASIS WEB (STUDI KASUS JATI INDAH FURNITURE) - Halim, Alfredo Oka; Wicaksono, Soetam Rizky (Kurawal - Jurnal Teknologi, Informasi dan Industri, 2023)
Many companies still do not have an information system in managing their business. With an information system, it is easier for companies to carry out processes and records that occur. UD Jati Indah Furniture is a company engaged in the field of household furniture, where the company has custom products according to customer requests. So in this study, a special production information system was created for custom products whose processes include product design, product references, work orders (SPK), goods delivery letters (SPB), estimated raw material prices due to changing prices, accessory costs, operational costs and other costs. The process stages in this system are from customer orders to delivery of goods. Payments made by customers are full payments. The method used is Waterfall which includes Requirement Analysis, Design and Implementation. In addition, this system also contains cash flow reports, stock card reports, reports on purchasing raw materials, accessories and operational tools.